Dissimilar joining of Ti–6Al–4V to 316L stainless steel by a novel joining process based on arc additive manufacturing and combined twin-wire arc welding - Lianhai Hu; Lixiang Lu; Mengqiu Ouyang; Shiqing Ma; Yongfu Chen; Yufeng Zhang; Yanan Gao; Guodong Tao (Journal of Materials Research and Technology)
The joining structure of Ti–6Al–4V to 316L stainless steel has potential demands in many fields. However, it is very difficult to avoid the formaiton of intermetallic compounds (IMCs) of the weld between Ti–6Al–4V to 316L stainless steel, which will severely decrease joint properties. In this paper, a novel joining technology that combines the single wire backing arc welding and the spatially arranged combined twin-wire arc welding was utilized to join Ti–6Al–4V and 316L stainless steel. Copper alloy wire (S214) and vanadium alloy wire (V01) were used as filler metals to produce two isolation layers, which prevented the formation of IMCs. The phase compositions at the Fe/Cu, Cu/V and V/Ti interfaces were Fe(S,S) + Cu(S,S), Cu(S,S) + V(S,S) and V(S,S)+(β-Ti, V)SS respectively. The distribution of the spherical and clustered V(S,S) particles in the matrix at the Cu/V interface contributes to dispersion strengthening and solid solution strengthening of the interface. Tensile strength of 394 MPa with an elongation of 2.53% was achieved. The joint fractured at the Cu/V interface of the single wire backing arc weld and the Cu zone of the spatially arranged combined twin-wire arc weld respectively. Dimple plastic fracture modes were detected in the joints. This technology is not only applicable to Ti–6Al–4V titanium alloy/316L stainless steel dissimilar metal joining, but also provides a new research strategy for the joining between other dissimilar metals.